Modern contracts, image transfer and causa: Analysis of sponsorship agreement - Stanojević Petra Z. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2025)
The paper focuses on specific kinds of contracts conducted with marketing purpose in mind - image transfer. The sponsorship agreement is interesting in a way that economic interests of the parties or the purpose of entering the agreement are so important that they dictate the way the contract should be analysed, as well as question the dominant idea of the relationship between causa and motive. Suggestions on how this contract should be regulated will be made towards the conclusion. The importance of discussing this topic consists in lack of regulation and theoretical works as well as its frequency and legal uncertainty in case of dispute.